2020
DOI: 10.3390/jcm9041190
|View full text |Cite
|
Sign up to set email alerts
|

The Skin Microbiota and Itch: Is There a Link?

Abstract: Itch is an unpleasant sensation that emanates primarily from the skin. The chemical mediators that drive neuronal activity originate from a complex interaction between keratinocytes, inflammatory cells, nerve endings and the skin microbiota, relaying itch signals to the brain. Stress also exacerbates itch via the skin–brain axis. Recently, the microbiota has surfaced as a major player to regulate this axis, notably during stress settings aroused by actual or perceived homeostatic challenge. The routes of commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 170 publications
0
27
0
Order By: Relevance
“…Additionally, influenced from HBDs and LL-37, mast cells liberate histamine and prostaglandin D 2 causing pruritus. 28…”
Section: The Skin Microbiome and Itchmentioning
confidence: 99%
“…Additionally, influenced from HBDs and LL-37, mast cells liberate histamine and prostaglandin D 2 causing pruritus. 28…”
Section: The Skin Microbiome and Itchmentioning
confidence: 99%
“…Activates Mast cells via MRGPRX2 47,81,91 S. aureus Protease Activates KCs via PAR-2 92 S. aureus and S. pyogens S. aureus activates KCs via TLR2. 47,93,94 Sensory neurons recognize N-formylated peptides and a-haemolysin from S. aureus 96 Scabies itch: an update proteases that activate immunocytes and nerves. 51 PARs on sensory neurons and immunocytes can mediate itch by interacting with proteases.…”
Section: S Aureus D-toxinmentioning
confidence: 99%
“…Compared with IgE-FceRI signalling, MRGPRX2-activated mast cells release more tryptase and excite PAR-2 and MRGPRX2 on neurons and lead to itch sensations. 80 MRGPRX2 is a receptor for a magnitude of substances and is activated by the following: (1) S. aureus d-toxin, 47,81,91 (2) protease and AMP (i.e. ß-defensin) produced by the KCs, 35,[52][53][54] (3) substance P from sensory neurons, 169 (4) eosinophil granule proteins (i.e.…”
Section: Host Responsementioning
confidence: 99%
“…As discussed in the introduction, the itch-scratch cycle plays a detrimental role in aggravating epidermal barrier defect, immune dysregulation, and microbial dysbiosis in AD. However, the latest literature reports suggested that the dysbiotic skin microbiome itself was an important factor stimulating itch [132].…”
Section: The Influence Of Skin Microbiome Dysbiosis On Itchmentioning
confidence: 99%
“…As regards AD, damaged keratinocytes and skin microbes upregulate pro-inflammatory cytokines, proteases, and neuropeptides that stimulate peripheral nerve fibers, thus causing the sensation of itch [132]. Seemingly, in the case of AD this process is largely triggered by S. aureus.…”
Section: The Influence Of Skin Microbiome Dysbiosis On Itchmentioning
confidence: 99%